Reconceptualizing Legal Protection of the Human Mind and Nervous System in the Era of Brain Computer Interface Technology - Joko Hadi Santoso; Ahmad Syahri; Adzkia Hitanaki; Lailasari Ekaningsih (Yayasan Cendekia Gagayunan Indonesia, 2025)
The rapid development of Brain–Computer Interface (BCI) technology enables direct interaction between the human brain and computational systems, offering substantial benefits in healthcare, education, and human capability enhancement. However, this technology also poses serious risks to the integrity of the human mind and nervous system, particularly through potential manipulation, unauthorized access to neural data, and violations of cognitive freedom. This study aims to reconceptualize the legal protection of the human mind and nervous system within the Indonesian legal framework in response to the emerging risks of BCI misuse. Employing normative legal research with a statutory and conceptual approach, this study analyzes Indonesian legal instruments, including human rights, personal data protection, electronic information, and health regulations, in conjunction with the evolving concept of neurorights. The findings reveal a significant normative gap, as existing regulations provide only fragmented and indirect protection and do not explicitly recognize neurodata or cognitive rights as distinct legal interests. Consequently, legal certainty and effective protection against BCI misuse remain inadequate. This study concludes that Indonesia urgently needs progressive legal reform by recognizing neurodata as a special category of sensitive data, explicitly incorporating neurorights into its legal system, and establishing a binding ethical and legal framework for neurotechnology. Such reconceptualization is essential to ensure that technological advancement aligns with the protection of human dignity, mental autonomy, and freedom of thought in the neurodigital era.